Influence of Aikido and Taijiquan-Tuishou on Contact Improvisation - Gómez-Lozano, Sebastián; Vargas-Macías, Alfonso; Kelly-Lahon, Clare; León, Kiko; García-Sottile, María Eugenia (Frontiers in Communication, 2022)
Oriental Martial Arts such as Taijiquan-Tuishou and Aikido represent some of the Asian influences on western culture resulting from immigration from China and Japan to the United States of America during the middle of the twentieth century. Contact Improvisation, a style of post-modern dance performed in pairs, is one of the manifestations enriched with this oriental influence. The purpose of this manuscript is to document which dynamic, proprioceptive and somatic elements were transferred to the choreographic language of Contact Improvisation from these martial arts. In the case of Contact Improvisation, the most important technical components highlighted include: centre of gravity, weight sharing, point of contact, sphericity, rolling, the embryonic relationship of axial axis and limbs, ki and proprioceptive communication. Although an evolution in the interpretation of the meanings and uses of this particular dance form may exist, we can nonetheless establish some kinaesthetic communication codes and strategies derived directly from its original sources. These sources belong to martial arts such as Aikido and Tuishou or Tajiquan and are essential to the intercultural communication component of the Contact Improvisation duo since they involve the learning of fundamentals and principles of non-verbal interaction considered as specific for the mastery of intercorporality. This is discussed in light of the work of Mark Young, a CI choreographer who maintains Paxton's legacy of roll technique documented in “Material for the Spine” by perfecting the execution and technical variations of helix rolls in a constructed system of spirals. This concurrence of strategies adopted from Aikido and Taijiquan and the usefulness of these elements in terms of performing this partner dance would appear to be key in the understanding of Contact Improvisation.